Membangun Kesadaran Global Warga Negara: Studi Kebijakan Publik Di Era Pandemi Covid 19 - Surya Dharma (PERSPEKTIF, 2021)
Currently the world is faced with various global problems that affect the lives of citizens both at the local and national levels. For example, how global warming affects rural agriculture. Forest burning that occurs in one area causes bad air in other areas and even crosses between countries. Likewise with the covid-19 virus pandemic which affects public health globally. These global problems can only be resolved collaboratively by involving all parties. As citizens, it is necessary to have awareness of the importance of caring, empathy and high solidarity with various global problems. This overall attitude is reflected in behavior that shows adherence to various policies issued by the government in an effort to prevent and resolve various global problems. This paper aims to identify, map and analyze various academic discourses from empirical studies regarding the relevance of public policies in the Covid-19 Pandemic era to the global awareness of citizens. The method used is literature study. The results show a synthesis that citizen participation in various policies related to the prevention and handling of the Covid-19 virus is highly dependent on public awareness as part of the global community.